Narasi Kristiani dalam syair Bugi’: Kajian terhadap simbolisme dan makna religius - Ismail Banne Ringgi; Silprilimian Mariu (KURIOS, 2026)
This study aims to uncover Christian narratives embedded in bu-gi' poetry, focusing on the symbolism and religious meanings in its texts. Bugi’s poetry is a traditional oral literary form of the Toraja people, rich with gospel values within cultural expression, yet it has not been theologically interpreted in Christian terms despite its practice in Christian celebratory ceremonies. This qualitative study was conducted in Sarira Village, Tana Toraja Regency, involving three purposively selected informants. Data were collected through in-depth interviews and analyzed using a hermeneutical approach to interpret the religious symbols within the poetry. Findings reveal that Christian values such as love, respect, hospitality, proclamation of God's goodness, joy, and blessing are expressed through metaphors and narrative structures in the poetry. Natural symbols, including celestial bodies, water, and wind, represent aspects of Christian teaching that have undergone inculturation within the local Torajan tradition. These findings affirm that Bugi’s poetry serves as a space of encounter between Christian faith and local wisdom, contributing to interdisciplinary studies that link regional literature, contextual theology, and cultural anthropology in Indonesia.   Abstrak Penelitian ini bertujuan mengungkap narasi Kristiani dalam syair Bugi’, dengan fokus pada simbolisme dan makna religius yang terkandung dalam teks syair. Syair Bugi’ merupakan sastra lisan tradisional masyara-kat Toraja yang sarat nilai-nilai Injil dalam budaya, namun selama ini be-lum dimaknai secara Kristiani meskipun telah dipraktikkan dalam upaca-ra sukacita orang Kristen. Penelitian kualitatif ini dilaksanakan di Kelurahan Sarira, Kabupaten Tana Toraja, melibatkan tiga informan yang dipilih secara purposif. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan pendekatan hermeneutik untuk menafsirkan simbol-simbol religius dalam syair. Hasil penelitian menunjukkan bahwa nilai-nilai Kristiani seperti kasih, penghormatan, hospitalitas, proklamasi kebaikan Tuhan, sukacita, dan berkat hadir melalui metafora dan struktur naratif syair. Simbol-simbol alam seperti benda langit, air, dan angin merepresentasikan aspek ajaran Kristiani yang telah mengalami inkulturasi dengan tradisi lokal Toraja. Temuan ini menegaskan bahwa syair Bugi’ berfungsi sebagai ruang perjumpaan antara iman Kristiani dan kearifan lokal, sekaligus memberikan kontribusi bagi studi interdisipliner antara sastra daerah, teologi kontekstual, dan antropologi budaya di Indonesia.